2014
DOI: 10.1364/ao.53.002037
|View full text |Cite
|
Sign up to set email alerts
|

Dual-view integral imaging 3D display using polarizer parallax barriers

Abstract: We propose a dual-view integral imaging (DVII) 3D display using polarizer parallax barriers (PPBs). The DVII 3D display consists of a display panel, a microlens array, and two PPBs. The elemental images (EIs) displayed on the left and right half of the display panel are captured from two different 3D scenes, respectively. The lights emitted from two kinds of EIs are modulated by the left and right half of the microlens array to present two different 3D images, respectively. A prototype of the DVII 3D display i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The more pinholes in the pinhole array used, the smaller the viewing angle becomes [8]. The viewing angle is also inversely proportional to the aperture width of the pinhole [9,10]. To offset the effect of the number of the pinholes, the horizontal aperture width of the rectangular pinhole is smaller than the vertical one.…”
Section: Principle and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The more pinholes in the pinhole array used, the smaller the viewing angle becomes [8]. The viewing angle is also inversely proportional to the aperture width of the pinhole [9,10]. To offset the effect of the number of the pinholes, the horizontal aperture width of the rectangular pinhole is smaller than the vertical one.…”
Section: Principle and Structurementioning
confidence: 99%
“…Moreover, the II display using the pinhole array is easily in realizing a compact 3-D-2-D convertible display system [6]. A number of studies related to the viewing angle have been reported [7][8][9][10]. For a single pinhole, the viewing angle is determined by the pitch of the pinhole and the gap between the pinhole and the elemental image [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we combine the multiview-zone display with the II 3D display, the multi-view-zone 3D display can provide different 3D images for different viewers in different view-zones at the same time. Recently, our group has proposed three methods to realize the multi-view-zone 3D display [11][12][13]. In the first method, each elemental image is divided into left and right parts; the viewing zones are narrow and not separated completely [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have proposed two dual-view II three-dimensional (3D) displays [11,12]. They present two different 3D images in the left and right viewing directions, respectively.…”
Section: Introductionmentioning
confidence: 99%